Peningkatan Ketahanan Pangan Berbasis Security Menggunakan Metode Eco-Enzyme Pada Perkebunan Sayuran - Iskandar Zulkarnaen; Eskar Tri Denatara; Anik Budiati; Juli Nurani; Yana Kusnandi Srijadi; Iwan Abadi; Pujo Iswahyudi; Argya Satyadini Mangku Praja (Jurnal Kajian Ilmiah, 2023)
The accumulation of rubbish in temporary dumps in market areas poses a threat to the surrounding environment. The market waste that accumulates is in the form of organik and non-organik waste that comes from leftover market traders. Organik waste in the market has become waste because vegetables and fruit are no longer suitable for consumption. This research aims to make organik fertilizer that is environmentally friendly and provides food security for farmers on vegetable plantations. This research method uses a security-based eco-enzyme method for utilizing organik waste into organik fertilizer in the form of liquid. This research has found a way to make eco-enzyme organik fertilizer which was carried out for 1 month from the fermentation process to testing at the local laboratory. 904 kg of organik waste that has been sorted for 7 days has produced 50 liters of liquid organik fertilizer. This research has resulted in food security as community independence in providing organik fertilizer derived from organik vegetable and fruit waste. The increase in food security that has been produced in each green mustard harvest is 14%. So that the use of organic waste in the form of vegetables and fruit into environmentally friendly organic fertilizer, can preserve the local environment and reduce air pollution.